THE INFECTIONS of HBV, HCV and HDV in RENAL TRANSPLANT RECIPIENTS - Ercan OK; Mahmut TÖBÜ; Evren ÖZDEMİR and Fehmi AKÇİÇEK and Yaman TOKAT and Serhat BOR and Gürhun ATABAY and Yücel BATUR (Turkish Journal of Gastroenterology, 2020)
-